Design and implementation of the new scintillation light detection system of ICARUS T600 - Ali-Mohammadzadeh, B.; Babicz, M.; Badgett, W.; Bagby, L.; Bellini, V.; Benocci, R.; Bonesini, M.; Braggiotti, A.; Centro, S.; Chatterjee, A.; Cocco, A.G.; Diwan, M.; et al. (Journal of instrumentation, 2020)
ICARUS T600 is the far detector of the Short Baseline Neutrino program at Fermilab (U.S.A.), which foresees three Liquid Argon Time Projection Chambers along the Booster Neutrino Beam line to search for LSND-like sterile neutrino signal. The T600 detector underwent a significant overhauling process at CERN, introducing new technological developments while maintaining the already achieved performances. The realization of a new liquid argon scintillation light detection system is a primary task of the detector overhaul. As the detector will be subject to a huge flux of cosmic rays, the light detection system should allow the 3D reconstruction of events contributing to the identification of neutrino interactions in the beam spill gate. The design and implementation of the new scintillation light detection system of ICARUS T600 is described.